Effectiveness of Criminal Law Enforcement against Corporations: Procedural Analysis and Mechanisms of Cross Country Criminal Justice - Tumian Lian Daya Purba; Silvester Magnus Loogman Palit (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Corporations as legal entities play a significant role in social, economic, and political dynamics. Alongside the increasing incidence of corporate crimes, the recognition of corporations as subjects of criminal law has become crucial. This study examines corporations as subjects of criminal law through a comparative analysis of Indonesia, the United States, and the Netherlands. The primary focus is on the differences in the concept of corporate criminal liability and the legal models applied. The research employs a normative juridical approach with a comparative study method. The findings reveal fundamental differences in the application of corporate criminal liability across the three countries, particularly regarding principles and forms of liability. The United States implements a more stringent principle of vicarious liability, the Netherlands has specific provisions in its Criminal Code (Wetboek van Strafrecht) that comprehensively accommodate corporate liability, whereas Indonesia still adopts a sectoral approach and lacks an integrated system. This study is expected to contribute to the strengthening of corporate criminal law policy in Indonesia.